1991
DOI: 10.1099/00221287-137-4-977
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence analysis of a plasmid-encoded chloramphenicol acetyltransferase gene from Staphylococcus intermedius

Abstract: The chloramphenicol acetyltransferase gene (cat) of a 3.9 kb chloramphenicol resistance (CmR) plasmid from Staphylococcus intermedius, designated pSCSl, was cloned into an Escherichia coli plasmid vector. Sequence analysis revealed a high degree of base similarity with the cat gene of the S. aureus CmR plasmid pC221 but there were several differences in the regulatory region. A lesser degree of similarity was observed between the cat gene of the S. intermedius plasmid and the cat gene of the S. aureus plasmid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 21 publications
(21 reference statements)
1
24
0
1
Order By: Relevance
“…The pSCS7-encoded CAT monomer was slightly smaller than the previously determined CAT monomers in staphylococci, which ranged between 215 and 219 amino acids (2,3,13,22,25,28). Comparisons revealed that the cat gene of pSCS7 exhibited 90% nucleotide sequence homology and 85% amino acid identity to the cat gene of pSCS5.…”
Section: Downloaded Frommentioning
confidence: 89%
See 4 more Smart Citations
“…The pSCS7-encoded CAT monomer was slightly smaller than the previously determined CAT monomers in staphylococci, which ranged between 215 and 219 amino acids (2,3,13,22,25,28). Comparisons revealed that the cat gene of pSCS7 exhibited 90% nucleotide sequence homology and 85% amino acid identity to the cat gene of pSCS5.…”
Section: Downloaded Frommentioning
confidence: 89%
“…The enzyme responsible for the acetylation was often found to be encoded by extrachromosomal, mobile DNA elements (17,29). In staphylococci, Cmr is the only known resistance marker, which is, to the best of our knowledge, exclusively located on plasmids (17,(25)(26)(27)(28). In gram-negative bacteria, the determinants for Cmr have also been found to be associated with plasmids or transposons (1,18,19,29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations